Layerwise stratification and band reordering in twisted multilayer MoTe 2 - Yueyao Fan; Xiao-Wei Zhang; Yusen Ye; Xiaoyu Liu; Chong Wang; Kaijie Yang; Di Xiao; Ting Cao (Proceedings of the National Academy of Sciences, 2026)
We introduce a physics-informed training-data generation strategy that efficiently captures the complete interlayer interactions in multilayer moiré systems, enabling a machine-learning force field transferable across layer numbers and stacking configurations, beyond twist angles. Applying this to multilayer twisted MoTe 2 (tMoTe 2 ), we identify a structural and electronic stratification: The two moiré interface (MI) layers retain substantial lattice reconstruction even in thick multilayers, while outer bulk-like layers show rapidly attenuated distortions. Surprisingly, this stratification becomes strongest not in the ultrasmall twist angle regime (≲1 ° ), where in-plane domain formation is well known, but rather at intermediate angles (2 to 5 ° ). Simultaneously, interlayer hybridization across the MI–bulk boundary is strongly suppressed, leading to electronic isolation. In twisted double bilayer MoTe 2 , this stratification gives rise to coexisting honeycomb and triangular lattice motifs in the frontier valence bands. We further demonstrate that twist angle and weak gating can create energy shift of bands belonging to the two motifs, producing Chern band reordering and nonlinear electric polarization with modest hole doping. Our approach allows efficient simulation of multilayer moiré systems and reveals structural–electronic separation phenomena absent in bilayer systems.